Association between some environmental risk factors and attention-deficit hyperactivity disorder among children in Egypt: a case-control study - Riham Abdelhamid Hussein; Rania Hussein Refai; Aleya Hanafy El-zoka; Hanan Galal Azouz; Mohamed Fakhry Hussein (Italian Journal of Pediatrics)
Abstract Background Attention-Deficit Hyperactivity Disorder (ADHD) is a complex disease that negatively impacts the social and academic/occupational activities of children and is more common in boys than in girls. Methods This case-control study aimed to assess the association between some environmental risk factors and ADHD among children in Alexandria, Egypt. It was carried out at the outpatient clinics of El Shatby Pediatric University Hospital in Alexandria, Egypt, with 252 children (126 cases and 126 controls). Hair samples were collected for analysis of lead and manganese levels using Atomic Absorption Spectrophotometer. A pre-designed interview questionnaire was used to determine the important environmental risk factors that may be related to ADHD. Results Children from parents with low levels of education, living in crowded houses, and occupational exposure to chemical agents were found to be risk factors for ADHD. The mean ± SD hair lead level in ADHD children was 2.58 ± 1.95, while in controls was 1.87 ± 0.92, with a statistically significant difference (p < 0.001). The mean ± SD hair manganese level in ADHD children was 2.10 ± 1.54, while in controls was 1.11 ± 0.69, with a statistically significant difference (p < 0.001). The logistic regression model revealed that six factors had a significant association with ADHD: using of newspapers to wrap food 3 or more times a week (adjusted odds ratio (AOR) = 105.11, 95% CI: 11.18-988.26), daily TV watching by child for more than 5 h (AOR = 63.96, 95% CI: 2.56-1601.32), child’s eating commercially packed noodles 3 times or more per week (AOR = 57.73, 95% CI: 3.77–593.93), using unpackaged flour in cooking (AOR = 44.47, 95% CI: 1.83–629.80), eating sweets daily by child (AOR = 6.82, 95% CI: 1.23–37.94), and lastly elevated hair Manganese level (AOR = 3.57, 95% CI: 1.24–10.29). Conclusions ADHD is a multi-factorial disorder, where many environmental risk factors contribute to its development. Future efforts to determine the best preventive strategy in Egypt must be based on a better knowledge of the role of environmental risk factors in the etiology of the disorder. Eliminating non-essential uses of lead and providing public education regarding the importance of safe disposal of lead-acid batteries and computers are necessary.